2021
DOI: 10.1371/journal.pone.0246144
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase modulates the microbiota of ileal mucosa and digesta of pigs fed corn-based arabinoxylans likely through both a stimbiotic and prebiotic mechanism

Abstract: The experimental objective was to characterize the impact of insoluble corn-based fiber, xylanase, and an arabinoxylan-oligosaccharide on ileal digesta and mucosa microbiome of pigs. Three replicates of 20 gilts were blocked by initial body weight, individually-housed, and assigned to 1 of 4 dietary treatments: a low-fiber control (LF), a 30% corn bran high-fiber control (HF), HF+100 mg/kg xylanase (HF+XY), and HF+50 mg/kg arabinoxylan oligosaccharide (HF+AX). Gilts were fed their respective treatments for 46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 74 publications
(93 reference statements)
1
34
0
Order By: Relevance
“…Increasing the AID of CP results in a reduction of the availability of undigested protein for microbial fermentation, thus reducing the abundance of proteolytic bacteria. In addition, the oligosaccharides released by xylanase and β-glucanase can modulate the mucosa-associated microbiota by selectively increasing the abundance of fiber-degrading bacteria ( Munyaka et al, 2016 ; Baker et al, 2021 ; Petry et al, 2021 ). A lower abundance of proteolytic bacteria such as Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the AID of CP results in a reduction of the availability of undigested protein for microbial fermentation, thus reducing the abundance of proteolytic bacteria. In addition, the oligosaccharides released by xylanase and β-glucanase can modulate the mucosa-associated microbiota by selectively increasing the abundance of fiber-degrading bacteria ( Munyaka et al, 2016 ; Baker et al, 2021 ; Petry et al, 2021 ). A lower abundance of proteolytic bacteria such as Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported that T cell populations are more abundant in the small intestine than in the large intestine in pigs at 8 wk of age, whereas it was similar in pigs at 4 wk of age. Petry et al. (2021) reported that the interaction among diet, microbiota, and immune system responses is more effective in the small intestine.…”
Section: Composition Of Intestinal Microbiotamentioning
confidence: 99%
“…Furthermore, the intestinal microbiota can be affected to different degrees in luminal and mucosal by the same factor ( Galley et al., 2015 ). According to Petry et al. (2021) , pigs fed high fiber diet had increased Erysipelotrichaceae , Olsenella , and Turibacter in the ileal lumen, whereas it increased Turibacter, Helicobacter, and Lachnospiraceae in the ileal mucosa.…”
Section: Composition Of Intestinal Microbiotamentioning
confidence: 99%
“…The stimbiotic effects include the speeding up development of a fiber-fermenting microbiome that gives a kickstart to the microbiome to ferment the fiber [ 48 ]. The prebiotic and stimbiotic mechanisms of xylanases have been recently described in pigs [ 49 ].…”
Section: Discussionmentioning
confidence: 99%